The Mindflow Method : How you can achieve anything by not-wanting and not-doing - Moegele, Tom (Carlsbad : Hay House, 2020)
The mindflow method is your key to finally overcoming anxiety, combating stress, and tackling emotional blocks, thereby releasing an infinite source of life energy. Through a powerful yet simple combination of movements, you can trigger energy shifts and reconnect to the natural flow of life.
Formerly CIP.
Also issued online.
Keywords: Self-actualization (Psychology); Stress management